(untitled) (Jurnal Teknologi (Sciences & Engineering), 2019)
Sesquiterpene synthase is an enzyme involved in sesquiterpene biosynthesis which catalyzed sesquiterpene formation from farnesyl diphosphate (FDP). In this research, the sesquiterpene synthase promoter (PmSS) was isolated from Persicaria minor (P.minor) to identify the functional region of the promoter and possible cis - regulatory element involved in the regulation of sesquiterpene synthase gene. Various putative cis - regulatory element involved in environmental stress and hormones were identified on PmSS promoter. The PmSS promoter and three series of deletion promoter were fused to Î²-glucuronidase (gus) gene and transformed into Arabidopsis thaliana. This study showed PmSS promoter was regulated in a developmental -specific manner and response to wounding, drought, heat, abscisic acid (ABA) and methyl jasmonate (MeJa) treatment. The results revealed the existence of cis regulatory elements that control the regulation of promoter activity in a developmental specific manner at -1758 to -1078 promoter sequences. The presence of cis-element acting as a repressor is expected to be present at the promoter between -1540 to -1078 bp. The region from -1078 to -855 was critical for maximal PmSS promoter activity. Deletion of promoter region from -1758 to -855 induced regulation of promoter in an organ-specific manner. Drought stress treatment did not induced GUS activity in deleted ABRE motif construct, suggested that ABRE motif is essential cis element during drought stress.Â Â